Development of corporate governance in Malaysia: Meeting practical and strategic sustainable needs - Arshad, Rozita; Mohd Mokhtar, Sany Sanuri (2013)
Recognition on the important of good corporate governance practices as a strategic sustainable of governance around the world is undeniable.A series of financial crisis and economic turmoil which have threatened capital markets and economies around the world are believed due to corporate governance weaknesses.Thus, the action to encounter this challenge in improving corporate governance is a significance agenda by the policy maker in upholding growth, development and sustainability of Malaysian economic.This paper describes the development of corporate governance in Malaysia and to identify the practical and strategic sustainable governance practices and thus provides conceptual framework in the development of corporate governance.